Pandemic insurance through pandemic partnership bonds: A fully funded insurance solution in a public private partnership - Helmut Gründl; Fabian Regele (Leibniz Institute for Financial Research SAFE, 2020)
This Policy Letter outlines a pandemic insurance solution through a pandemic-related 'Insurance Linked Bond'. It would be originated by governments, with a principal amount to cover significant costs resulting from a pandemic. These bonds, which would be traded on a secondary market, generate a risk-adequate return for private and institutional investors that is financed through the insurance premiums paid by the public domain. In case of a pre-defined pandemic trigger event, the principal of the bond becomes available for the originating governments to cover pandemic-related costs. Through this approach, governments can insure themselves against future pandemic-related risks, while funding comes primarily from private and institutional investors.
urn:nbn:de:hebis:30:3-534499
Keywords: 330; Covid-19-Crisis; catastrophe bond; public private partnership; pandemic insurance